High-output diesel engine heat transfer: Part 2 – instantaneous spatially averaged heat transfer correlation. (September 2022) - Gingrich, Eric; Tess, Michael; Korivi, Vamshi; Ghandhi, Jaal
A new temporally resolved spatially averaged heat transfer correlation was developed using the local piston heat flux data presented in the first part of this paper. The new correlation extends previous correlations that relate the Nusselt and Reynolds numbers through a power law by adding a dimensionless chemical energy release rate term. The new term, which arises from dimensional analysis, should enable similitude for diesel engines. Additionally, the characteristic velocity used in the Reynolds number was modified to include the integrated fuel mass injection rate. The new correlation was calibrated to the experimental data by minimizing the least squares error, and compared to existing correlations from the literature. On average, the new formulation was found to match the experimental data better than the existing models even when the existing models' constants were adjusted to best fit the measured data.